Molecular docking and dynamics simulations of bioactive terpenes from Catharanthus roseus essential oil targeting breast cancer - Nayila Iffat; Sharif Sumaira; Ullah Riaz; Alotaibi Amal; Shah Syed Ali Raza; Bibi Maira; Hameed Saima; Iqbal Aasma (Open Chemistry)
Medicinal plants have been used against diseases due to their protective and curative role since undocumented history. Approximately 50% of anticancer drugs are based on phytoconstituents of medicinal plants. Many bioactive substances with diverse pharmacological activities identified from Catharanthus roseus medicinal plant are actively used against cancer.